DEPRESI EKONOMI DUNIA 1929-1935: PERUBAHAN DASAR EKONOMI, HALA TUJU DAN INVOLUSI PERTANIAN DI PULAU JAWA - Dr. Nazarudin Zainun (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
The economy of the East Indies once had been developed for 3 decades started at the beginning of the 20th century. The growth of agricultural sector made East Indies as once of the most important corps export countries in the world at that time. The economic rapid development for the 3 decades had allowed the indigenes to enjoy a better quality of life.At the peak development of East Indies in 1929, there was economic depression that cause the corps production of East Indies did not sell well in the world market. It caused the collapse of private agricultural companies followed by the decline of the indigenes’ life level. They turned into poor people in sudden. In order to address this problem, the government took drastic step by tightening the budget. Thus it caused the change of basic economy of East Indies government, from free trade into enonomic interference. The budget cut automatically happened, yet efficient acts did not taken immediately.Budget cut in terms of subsidy caused the sugar cane fields turned into rice fields. But irrigation problem retarded the growth of rice in the fields. At the same time the number of farmers increased steadily because of the discharge of sugar cane fields’ and factories’ labors. The labors who are not accommodated into other sectors accumulated in rice field sector. Because the output was still the same while the labors increased, the productivity per labor actually decreased. This was the sign of beginning of agricultural involution in Java Island. Thus, economic depression in 1929 has lead to the long-term effect on East Indies Governmant, and none of their efforts were success in managing the bad situation caused by the depression.